Source combined linear predictive analysis in pulse-based speech coders - Hasib, A; Hacioglu, K (Iee-Inst Elec Eng, 1996)
The conventional linear predictive analysis in pulse-based coders is replaced by the so-called source-combined linear predictive method to match the excitations considered in two steps: synthesis filter determination and excitation search. It differs from Atal's two-pass approach in that the synthesis filter is optimised jointly with the excitation prior to the ABS excitation search. However, it is a difficult task eo obtain the optimum solution, and, thus, a suboptimal algorithm is developed. Initially, the algorithm starts with the covariance method and then corrects the synthesis filter using an estimate of the excitation. This is accomplished by using two coupled equations originally developed. The effectiveness of the approach in multipulse and regular pulse excited coders is demonstrated. Extensive simulation results, at several bit rates, with different excitations, are presented. Comparisons are made with the standard coder and the coder that employs Atal's approach. In all conditions, the proposed coder is found to give better results.
Keywords: speech coders; linear predictive analysis; algorithms; noise; filtering